Investigating Greek EFL Coordinators’ Involvement in Online Elteachers Communities of Practice as a Means of Professional Development - Kourkouli, Katerina (European Journal of Social Science Education and Research, 2021)
This paper examines Greek EFL Coordinators’ involvement in online ELTeachers Communities of Practice (CoPs) and its impact on their own and their trainees’/teachers’ professional development. The study focuses on four (4) Greek EFL School Advisors who acted as Coordinators of four online CoPs training fourty-nine (49) EFL teachers using an online platform named 2gather developed by the University of Athens in the context of a national in-service professional development project in Greece. Founded on the theory of situated learning, CoPs have been defined as “groups of people who share a concern, a set of problems, or a passion about a topic, and who deepen their knowledge and expertise in this area by interacting on an ongoing basis” (Wenger et al., 2002). The study involved monitoring the development of four online ELTeachers CoPs and their respective Coordinators’ patterns of involvement and response using a mixed-methods approach which combined quantitative data and qualitative research of collective case studies (Dornyei, 2007) of the four groups of teachers. A comparison of the Coordinators’ implementation of meaningful professional development (Franke et al., 2001) activities “before” and “after” their involvement in the online CoPs was carried out. Findings delineate the extent of the Coordinators’ “reformed” training practice in terms of professional development activities provided to the teachers “before” and “after” their CoP involvement as well as their report on their teachers’ and their own perceived benefit. Results also highlight the role of the Coordinators’ attitude towards the innovative model of teacher education for its feasibility and viability in Greece and contribute to furthering our understanding of effective implementation of online CoPs in the context of continuing professional development.
Keywords: professional development, online communities of practice, effective implementation, reformed training practice